Effort of lower hybrid current drive experiments toward to H-mode in EAST. (17th November 2016) - Ding, B.J.; Li, M.H.; Liu, F.K.; Shan, J.F.; Li, Y.C.; Wang, M.; Liu, L.; Zhao, L.M.; Yang, Y.; Wu, Z.G.; Feng, J.Q.; Hu, H.C.; et al.
Abstract: Lower hybrid current drive (LHCD) is an effective tool to achieve high confinement (H-mode) plasma in EAST. To utilize LHCD for accessing H-mode plasma, efforts have been made to improve LHW (lower hybrid wave)-plasma coupling and current drive capability at high density. Improved LHW-plasma coupling by means of local gas puffing and gas puffing from the electron side is routinely used during EAST operation with LHCD. High density experiments suggest that low recycling and high LH frequency are preferred for LHCD experiments at high density, consistent with previous results in other machines. The effect of LHCD on the current profile in EAST demonstrates that it is possible to control the plasma profile by optimizing the LHW spectrum. Repeatable H-mode plasma was obtained by LHCD and the maximum density during H-mode with the combination of 2.45 GHz and 4.6 GHz LH waves was up to 4.5 × 10 19 m −3 .